You should buy 576 grams of cereal. I believe this is right because 32g x 18=576. But you might want me to work it different or something.
Answer: To find the inverse of the function, we need to make x as a function of y and at the final step make a switch between x and y (i.e. make x as y and y as x)
y = x² + 4x + 4 ⇒⇒⇒ factor the quadratic equation
y = (x+2)(x+2)
y = (x+2)² ⇒⇒⇒ take the square root to both sides
√y = x+2
x = √y - 2 ⇒⇒⇒ x becomes a function of y
final step:
∴ y = √x - 2 ⇒⇒⇒ the inverse of the given function
So, as a conclusion:
f(x) = y = x² + 4x + 4 ⇒⇒⇒ the given function
f⁻¹(x) = y = √x - 2 ⇒⇒⇒ the inverse of the given function
Answer:
£21552.
Step-by-step explanation:
Given information:
Principal amount = £18790
Rate of simple interest =4.9% = 0.049 per year
Time = 3 years
Formula for simple interest:
where, P is principal, r is rate of interest and t is time in years.
Total amount after 3 year is
Therefore, Dan have £21552 after 3 years.
By applying the segment addition postulate, the <u>value of v = 7</u>
- According to the Segment Addition Postulate, it holds that if point C is between points D and E, therefore:
DC + CE = DE
![DC = 2v-15\\\\CE = 3v-8\\\\DE = 27](https://tex.z-dn.net/?f=DC%20%3D%202v-15%5C%5C%5C%5CCE%20%3D%203v-8%5C%5C%5C%5CDE%20%3D%2027)
- Therefore, by substitution, we will have the following equation:
![(2v-15) + (3v-8) = 27](https://tex.z-dn.net/?f=%282v-15%29%20%2B%20%283v-8%29%20%3D%2027)
- Open the bracket and solve for the value of v.
![2v-15 + 3v-8 = 27](https://tex.z-dn.net/?f=2v-15%20%2B%203v-8%20%3D%2027)
![5v - 23 = 27](https://tex.z-dn.net/?f=5v%20-%2023%20%3D%2027)
![5v - 23+ 23 = 27 + 23\\\\5v = 50](https://tex.z-dn.net/?f=5v%20-%2023%2B%2023%20%3D%2027%20%2B%2023%5C%5C%5C%5C5v%20%3D%2050)
v = 10
Therefore, using the segment addition postulate, the <u>value of v = 10</u>
Learn more about the segment addition postulate here:
brainly.com/question/1721582
Answer:
<u>The simplest radical form of this mathematical expression is - 3√3</u>
Step-by-step explanation:
1. Let's write in a mathematical expression the information given:
-4 the square root of 12 + the square root of 75
-4 (√12) + √75
-4 (√4 * 3) + (√25 * 3) (12 = 4 * 3 and 75 = 25 * 3)
-4 (2 √3) + 5 √3
-8 √3 + 5√3
- 3 √3
The result is- 3 square root of 3.
<u>The simplest radical form of this mathematical expression is - 3√3</u>